Effect of cerebrolysin on motor function restoration during medical rehabilitation - M. A. Kustova (Nevrologiâ, Nejropsihiatriâ, Psihosomatika, 2016)
Ischemic stroke (IS) is characterized by high prevalence, mortality, and disability rates. Therapy aimed to correct one biochemical or molecular stage of ischemic cell injury fails to treat stroke, suggesting that it is necessary to study multimodality therapy affecting several related pathophysiological components.The paper gives the January 2016 results of the randomized placebo-controlled multicenter study CARS that demonstrates the positive effect of cerebrolysin versus placebo according to the primary efficiency criterion, the Action Research Arm Test (ARAT) scale, and total outcome 90 days after disease onset. The investigation enrolled mainly patients with moderate or severe IS (the mean National Institutes of Health Stroke Scale score was 9 at baseline).The specific features of the CARS study versus those of other clinical trials of neuroprotectors were the initial planning of narrower end criteria of efficiency (arm motor function recovery whereas the major goal of many investigations was to reduce mortality rates), as well as a standardized rehabilitation program in both treatment groups. Such investigations did not previously take into account the nature and volume of rehabilitation measures although the latter may have a substantial impact on the outcome of stroke.The CARS study is the first among the previously conducted clinical trials of neuroprotectors, which has attained the primary objective (to restore motor function), which opens up fresh opportunities for the medical support of rehabilitation measures in patients with IS.